1998
DOI: 10.1007/bf02486471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interior and exterior insulation on the hygrothermal behaviour of exposed walls

Abstract: RESUMEMassive walls exposed to the natural climate without special rain protection show a dynamic moisture equilibrium governed by the alternating events of rain and sunshine. The moisture further reduces the rather low insulation level of the walls. Therefore, thermal insulation measures have to be taken in order to improve the hygienic conditions and the thermal performance of the building. The influence of interior and exterior insulations on the hygrothermal behaviour of such walls can be determined with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 0 publications
1
35
0
1
Order By: Relevance
“…In fact various authors (Barreira et al 2013;Flores-Colen et al 2008;Künzel 1998) have studied the development of stains, especially those associated with surface condensation, to try and scientifically explain their occurrence and also minimise them. Other anomalies related to wall colour occur significantly less often than those mentioned above, e.g.…”
Section: Incidence Of the Anomaliesmentioning
confidence: 99%
“…In fact various authors (Barreira et al 2013;Flores-Colen et al 2008;Künzel 1998) have studied the development of stains, especially those associated with surface condensation, to try and scientifically explain their occurrence and also minimise them. Other anomalies related to wall colour occur significantly less often than those mentioned above, e.g.…”
Section: Incidence Of the Anomaliesmentioning
confidence: 99%
“…The system is especially applied to high-rise residential buildings nowadays, since concrete in the interior space of building can sustain heat due to the heat storage effect when EIFS is activated [6][7][8][9]. Furthermore, the system can eliminate thermal bridge between wall and slab, which was always recognized as a problem to be resolved in case internal insulation method is adopted.…”
Section: Research Background and Purposementioning
confidence: 99%
“…If it is not properly done, this could lead to damages and in worst case building failure [13]. When adding insulation to the exterior, the existing structure is kept in a warm and dry condition which is beneficial from a moisture point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Straube et al [18] studied a number of brick buildings in the United States where interior insulation had been added and concluded that rain and water leakage issues have to be addressed properly and that there was a risk that wooden beam ends in the walls were damaged by the changed hygrothermal conditions in the wall. Also Künzel [13] showed that exterior walls insulated on the interior need to be combined with rain protection measures to avoid moisture induced damages. When retrofitting old buildings, the prerequisites are given by the existing construction.…”
Section: Introductionmentioning
confidence: 99%